2015
DOI: 10.1093/ntr/ntv187
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cotinine Levels Among Latino Tobacco Farmworkers in North Carolina Compared to Latinos Not Employed in Agriculture

Abstract: This study documents the heavy burden of nicotine exposure and dose experienced by tobacco workers in North Carolina. Hundreds of thousands of farmworkers and farmers in the United States and Canada, as well as agricultural workers around the world, share this burden of nicotine exposure and dose. These results support the need to change work practices and regulations to protect workers. They also document the need to delineate the health effects of long-term exposure to high transdermal nicotine doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Among female non-smokers, age may be a marker of the division of labor if older tobacco farmers reduce their participation in the harvest due to the high level of physical exertion required. The higher cotinine levels in female non-smokers who pick wet tobacco leaves is consistent with studies that indicate the role of water (moisture) in facilitating nicotine absorption 1 , 2 , 7 , given that it is soluble in both polar and non-polar substances.…”
Section: Discussionsupporting
confidence: 87%
“…Among female non-smokers, age may be a marker of the division of labor if older tobacco farmers reduce their participation in the harvest due to the high level of physical exertion required. The higher cotinine levels in female non-smokers who pick wet tobacco leaves is consistent with studies that indicate the role of water (moisture) in facilitating nicotine absorption 1 , 2 , 7 , given that it is soluble in both polar and non-polar substances.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted by Arcury et al ( 2016) [36] indicated that tobacco farmers had much higher levels of urinary cotinine (396.03 ng/mL) when compared to individuals who did not work in tobacco farming (9.03 ng/mL). Exposure to green tobacco leaves causes transdermal absorption of nicotine, thus increasing nicotine levels in the blood and resulting in GTS.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to green tobacco leaves causes transdermal absorption of nicotine, thus increasing nicotine levels in the blood and resulting in GTS. Nicotine is water-soluble [36], and as such, its absorption increases when harvesting leaves are wetted by morning dew or due to contact with transpiration. Absorption is also increased by not using personal protective equipment, by eventual impairment of the skin integrity, and vasodilation resulting from working in hot and humid environments [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The assay was performed by Salimetrics LLC using standard procedures. Details about the assays can be found in works published by Quandt et al [6] and Arcury et al [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Tobacco farmworkers can have systemic nicotine levels that are comparable to regular smokers [15, 16]. While it is known that large doses of nicotine are toxic [17, 18], many studies have indicated that lower, nontoxic doses of nicotine improve cognitive performance through modulating the release of several neurotransmitters including acetylcholine and dopamine [19, 20].…”
Section: Introductionmentioning
confidence: 99%